Association joint action for truth and reconciliation: Activities in 2006 and plans for the future - Nikolić-Ristanović Vesna; Bjelić Danijela (Temida)
In this paper the detailed overview of 2006 activities of Association Joint action FOR truth and reconciliation, as well as main directions of its expected actions in 2007, is given. During 2006 the activities of the Association were primarily oriented toward its own development, including defining aims and basic values, as well as empowerment and mutual support of its members. The second part of activities was oriented to the public promotion of the idea of "third way" and the Association itself. Activities in 2006 included: activities oriented toward development of Association, development of resource center and research, activities in direction of increasing social visibility of Association, as well as activities oriented toward development of cooperation and promotion of "third way" in other parts of the former Yugoslavia. .